EP501 Management of patients with metastatic endometrial cancer at diagnosis: single center experience. (1st November 2019) - Cordoba, A; Cerezo, E; Broyelle, A; Parent, A; Le Deley, M-C; Le Tinier, F; Escande, A; Lesoin, A; Chevalier, A; Lemaire, A-S; Taieb, S; Hudry, D; et al.
Abstract : Introduction/Background: Retrospective evaluation of a cohort of patients diagnosed with metastatic endometrial cancer (EC) and to describe the treatment performed as well as the rates of overall survival (OS), progression free survival (PFS) and survival without locoregional recurrence. Methodology: Between January 2002 and December 2018, all consecutive patients with EC stade IV were included; patients who did not receive any treatment (CT, RT or surgery) at the time of diagnosis were not included. All treatments performed [chemotherapy (CT), surgery and external radiotherapy (RT)] were collected. Results: 56 patients were identified; the median age of the patients was 64 years (39–83); the median follow-up of patients was 4.4 years 95% CI95% [3.4–6]. 53 patients (95%) IVb and 3 patients (5%) Iva. 42 patients (74%) had an endometroid or type 1 histology and 14 patients (26%) had a non-endometroid or type 2 histology. All patients (56) received CT. 37 patients (66%) had surgery, 23 (62%) before CT and 14 (38%) after CT. 25 patients (45%) received adjuvant RT after surgery. 4 patients (7%) presented local-locoregional recurrence, 18 patients (32%) presented metastatic and local-locoregional recurrence and 21 patients (37, 5%) isolated metastatic recurrence. The median survival time is 2.9 years 95% CI[1.7–4.8]. 5 year-OS is 33%. The median progression-free survival (PFS) rate is 1.5 years 95% CI [0.91–1.98]. 5 year-PFS is 19%. Cumulative incidence of local-regional recurrence at 1, 3 and 5 years is 17%, 41% and 45%. Conclusion: Metastatic EC presents poor prognosis. The use of surgery and adjuvant RT in addition to CT may improve OS, PFS and loco regional recurrence in selected patients. Disclosure: Nothing to disclose.